Fibrin–alginate hydrogel supports steroidogenesis, in vitro maturation of oocytes and parthenotes production from caprine preantral follicles cultured in group. (21st September 2016) - Brito, IR; Silva, GM; Sales, AD; Lobo, CH; Rodrigues, GQ; Sousa, RF; Moura, AAA; Calderón, CEM; Bertolini, M; Campello, CC; Smitz, J; Figueiredo, JR
Contents: This study aimed to establish a culture system that improves the in vitro development of caprine preantral follicles. In a first experiment, follicles were encapsulated as a single unit per bead and cultured singly or in groups or with five follicles in the same alginate (ALG) bead for 18 days. In a subsequent experiment, the "five follicles per bead" design was chosen to culture in ALG, fibrin–alginate (FA) or hyaluronate (HA) for 18 days. In a third experiment, we chose the five follicles per bead in FA to culture for 30 days. The culture set‐up of five follicles per ALG bead increased antrum formation and follicle diameter compared to the other culture designs ( p < .05). Moreover, under this condition, 44.44% of the oocytes from in vitro cultured preantral follicles reached meiotic resumption. A significant increase of follicle diameter occurred in attachment system and FA ( p < .05), but the ALG condition reached the highest among all groups on day 18 ( p < .05). Follicles encapsulated in matrix produced more estradiol and progesterone than attachment system ( p < .05). The expression of MMP‐9 mRNA was higher in FA than in other groups ( p < .05) and similar to antral follicles from in vivo control ( p > .05). Only FA group resulted in oocytes matured. After 30 days, oocytes from preantral follicles in vitro grown in FA developed to eight‐cell parthenotes. In conclusion, a culture system using FA supported the development of caprine preantral follicles cultured in group and included in the same bead of hydrogel, improving the oocyte maturation and producing parthenotes.